2010
DOI: 10.2298/abs1002479c
|View full text |Cite
|
Sign up to set email alerts
|

Food composition of some low altitude Lissotriton montandoni (Amphibia, Caudata) populations from North-Western Romania

Abstract: The diet of some populations of Lissotriton montandoni from north-western Romania is composed of prey belonging to 20 categories. The food components of the Carpathian newts are similar to those of other species of newts. Most of the prey are aquatic animals, but terrestrial prey also has a high percentage abundance. The consumed prey categories are common in the newts' habitats as well, but in natural ponds the prey item with the highest abundance in the diet is not the most frequent one in the habitat. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Dobre et al, 2007;David et al, 2009;Covaciu-Marcov et al, 2010a newts hunt in the aquatic habitat has been recorded previously (e.g. Denoël & Andreone, 2003;Kutrup et al, 2005;Vignoli et al, 2009;Covaciu-Marcov et al, 2010a, 2010b, and few exceptions have been documented (Cicort-Lucaciu et al, 2007a). The reduced food diversity of the newts is a consequence of the consumption of aquatic preys, which are probably less diversified in a small habitat.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Dobre et al, 2007;David et al, 2009;Covaciu-Marcov et al, 2010a newts hunt in the aquatic habitat has been recorded previously (e.g. Denoël & Andreone, 2003;Kutrup et al, 2005;Vignoli et al, 2009;Covaciu-Marcov et al, 2010a, 2010b, and few exceptions have been documented (Cicort-Lucaciu et al, 2007a). The reduced food diversity of the newts is a consequence of the consumption of aquatic preys, which are probably less diversified in a small habitat.…”
Section: Discussionmentioning
confidence: 84%
“…In recent years, several papers about the feeding of some amphibian species have been published from Romania (e.g. Aszalos et al, 2005;Balint et al, 2010;Cicort-Lucaciu et al, 2005, 2007a, 2007b, 2011Cogalniceanu et al 2000;Covaciu-Marcov et al, 2010a, 2010b, 2010c, 2011Dobre et al, 2007;Kovacs et al, 2007;Sas et al, 2009;Iftime & Iftime, 2011), but most have been from the north-western part of the country. The few data available regarding the south west focus only on some species (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In April, Analysis of regurgitated stomach contents including the empty stomachs (11.81%) showed that on average 9.9 ± 8.4 benthic macroinvertebrate items are consumed by N. microspilotus. Compared to similar values for prey diversity in other Caudata, Covaciu-Marcov et al (2010) have demonstrated that the Carpathian newt (Lissotriton montandoni) feeds on only 2.72 items. However, similar value for the great crested newt (Triturus cristatus) is 9.8 (David et al 2009).…”
Section: Discussionmentioning
confidence: 54%
“…Lissotriton montandoni females arrive at a pond at a time when smaller L. montandoni males and similarly sized I. alpestris males are already established in an aquatic environment; L. montandoni females also start to use resources at the same time with I. alpestris females. In the case of habitats lacking trophic resources, or characterised by the presence of a second species (in this case I. alpestris ), individuals may shift their foraging to a terrestrial environment (Covaciu-Marcov et al 2010 ). This switch might be easier adaptation for females, because they have no toe webbing and are characterised by a more massive shoulder girdle and more powerful jaws.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have also shown significant differences in head size between sexes in L. montandoni (Dandová et al 1998 ; Janiga and Mlichová 2004 ). Furthermore, it has been found that the stomach of L. montandoni males is more frequently empty, when compared to females, which might be associated with males’ higher motivation for mating than in feeding (Covaciu-Marcov et al 2010 ). Moreover, the size and nutrition of the female is closely linked to fertility (Hayes et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%